An Efficient Method for The Synthesis of Dihydropyridine by Hantzsch Reaction with Fe/SiO2 Nano Heterogeneous Catalysts - Ateeq Rahman; P. N. Nehemia; Moola M. Nyambe (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
An efficient method for the synthesis of dihydropyridines (DHPs) by Hantzsch reaction with Fe/SiO2 heterogeneous catalysts was developed. The Fe/SiO2 catalysts was prepared by impregnation method. The catalysts were characterized by IR and SEM instruments. The SEM results indicated that Fe/SiO2 nano spheres were formed. The reaction procedure involved reaction of aldehyde, ethyl acetoacetate (EAA), ammonium acetate (NH4OAc) and ethanol under reflux. The study was focused on optimizing reactions conditions: Standardization of catalyst, substrate of study and solvent study. In order to identify the best active catalysts, five different ratios of catalyst were synthesized and evaluated for the title reaction under similar conditions. To standardize the active catalysts, different temperature conditions (i.e. room temperature, 60 ºC and 80 ºC) as well as catalysts amounts were evaluated. Under these established conditions, 2.5% Fe/SiO2 was the best active catalysts that resulted. Benzaldehyde and p-anisaldehyde were used to study the effect of having various substrates on the conversion and reaction time, especially the substituted aldehydes. The best results were obtained by reacting p-anisaldehyde with EAA, NH4OAc and ethanol at 60 ºC with 0.3 grams of 2.5% Fe/SiO2 heterogeneous catalysts. Thin Layer Chromatography (TLC) monitoring of the reaction mixture showed no selectivity at high temperatures (80 ºC) with 15% Fe/SiO2. Standardization of solvent study was executed with two solvents, ethanol and acetonitrile. The product dihydropyridines were analyzed using gas chromatography-mass spectrometry (GC-MS). The melting points of the products were compared with authentic samples reported in the literature. Hence, the Fe/SiO2 catalysts is eco-friendly and economically developed for the title reaction. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).